An overview of public transport reliability studies using a bibliometric analysis - M.A. Alkubati, M.A. Alkubati; Nasradeen A. Khalifa, Nasradeen A. Khalifa; Hareth A. Al-barakani, Hareth A. Al-barakani (Asej, 2023)
Reliability in public transport is considered one of the most critical features to evaluate the service quality from the perspective of passengers, operators, and the community. Several studies have been published about public transport reliability. However, there are an absence of comprehensive and quantitative studies. Furthermore, only nine reviews related to public transport reliability have been published on the Web of Science (WOS) database. The current review was conducted to enrich researchers and practitioners with the update of public transport reliability publications through the last 15 years (during 2005–2021) to fulfil their concerns and answer their public transport reliability questions. This Bibliometric analysis aims to illustrate the concept of transportation reliability, highlight its lack of uncovered studies, and provide an overview of the most productive countries, journals, institutions in transportation reliability publications to support future studies and cooperation. A bibliometric analysis was performed using VOSviwer software analysis the public transport reliability publications obtained from the WOS database to enable researchers to trace the historical and annual records of publications related to reliability covering the leading countries, institutions, journals, most frequently used keywords, authors, citation network analysis and the most cited publications. The analysis findings show the dramatic annual growth of public transport reliability publications and identify the indicators and interested points of reliability.